2020
DOI: 10.1186/s43141-020-00055-5
|View full text |Cite
|
Sign up to set email alerts
|

Drug repurposing of nitazoxanide: can it be an effective therapy for COVID-19?

Abstract: Background: The current outbreak of pandemic coronavirus disease 2019 (COVID-19) aggravates serious need for effective therapeutics. Over recent years, drug repurposing has been accomplished as an important opportunity in drug development as it shortens the time consumed for development, besides sparing the cost and the efforts exerted in the research and development process. Main body of the abstract: The FDA-approved antiparasitic drug, nitazoxanide (NTZ), has been found to have antiviral activity against di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(80 citation statements)
references
References 79 publications
1
72
0
7
Order By: Relevance
“…This approach offers the advantage of minimizing the required time, cost, and efforts for drug discovery process and safety evaluation. Furthermore, it reduces the risk of the drugs to fail, particularly due to safety issues since the majority of drugs are repositioned after verifying their safety in preclinical and clinical studies [9,10]. At the same time, drug repositioning demands an extensive study concerning the drug profile and new targeted disease mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach offers the advantage of minimizing the required time, cost, and efforts for drug discovery process and safety evaluation. Furthermore, it reduces the risk of the drugs to fail, particularly due to safety issues since the majority of drugs are repositioned after verifying their safety in preclinical and clinical studies [9,10]. At the same time, drug repositioning demands an extensive study concerning the drug profile and new targeted disease mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…To rapidly define potential therapeutic options against SARS-CoV-2, testing existing Food and Drug Administration (FDA)-licensed drugs for efficacy against novel viral pathogens represents a practical approach for anti-CoV screening. This could expedite the recommendation and/or implementation of those FDA-approved drugs with effective anti-COVID-19 activity in the treatment protocol [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Nitazoxanide demonstrated strong broad antiviral in vitro and in vivo activity (38,45,46), with clinical evidence of consistent antiviral activity in humans for a wide variety of virus families (46), with o cial indication for gastrointestinal viruses. Speci c anti-SARS-CoV-2 activity in vitro and in vivo has also been extensively demonstrated (46)(47)(48), and its plausibility as a promising therapy for COVID-19 found the strongest evidence between the three drugs, particularly when combined with azithromycin (48). Despite slightly less tolerable in terms of symptoms compared to hydroxychloroquine and ivermectin, intolerance rates are low.…”
Section: Discussionmentioning
confidence: 99%
“…Given that SARS-CoV-2 does not encode any neuraminidase protein, neuraminidase inhibitors such as oseltamivir, zanamivir or lamivir are not thought to be effective for treating patients with COVID-19 . However, some studies have found that drugs including arbidol (Zhu et al, 2020), fusion peptide (EK1) (Xia et al, 2019), ganciclovir (Lai et al, 2020), Abelson (Abl) kinase inhibitor (imatinib) (Bernal-Bello et al, 2020), metronidazole (Gharebaghi et al, 2020), antiprotozoal drugs (nitazoxanide and ivermectin) (Mahmoud et al, 2020;Peña-Silva et al, 2020), and 3CL(Pro) inhibitors (Rathnayake et al, 2020) are efficacious when used to prevent SARS-CoV-2 infections in vitro. However, their safety and efficacy in preventing COVID-19 in humans remains to be determined.…”
Section: Other Drugsmentioning
confidence: 99%